Incidence of type 1 diabetes in children and adolescents during the COVID-19 pandemic in Germany: results from the DPV registry - Kamrath, Clemens; Rosenbauer, Joachim; Eckert, Alexander J.; Siedler, Kai; Bartelt, Heike; Klose, Daniela; Sindichakis, Marina; Herrlinger, Silke; Lahn, Valentina; Holl, Reinhard W. (Diabetes care, 2022)
The aim of this study was to investigate the incidence of type 1 diabetes in children and adolescents during the coronavirus disease 2019 (COVID-19) pandemic in Germany compared with previous years.Based on data from the multicenter German Diabetes Prospective Follow-up Registry, we analyzed the incidence of type 1 diabetes per 100,000 patient-years in children and adolescents from 1 January 2020 through 30 June 2021. Using Poisson regression models, expected incidences for 2020/21 were estimated based on the data from 2011 to 2019 and compared with observed incidences in 2020/21 by estimating incidence rate ratios (IRRs) with 95% CIs.From 1 January 2020 to 30 June 2021, 5,162 children and adolescents with new-onset type 1 diabetes in Germany were registered. The observed incidence in 2020/21 was significantly higher than the expected incidence (24.4 [95% CI 23.6-25.2] vs. 21.2 [20.5-21.9]; IRR 1.15 [1.10-1.20]; P < 0.001). IRRs were significantly elevated in June 2020 (IRR 1.43 [1.07-1.90]; P = 0.003), July 2020 (IRR 1.48 [1.12-1.96]; P < 0.001), March 2021 (IRR 1.29 [1.01-1.65]; P = 0.028), and June 2021 (IRR 1.39 [1.04-1.85]; P = 0.010).A significant increase in the incidence of type 1 diabetes in children was observed during the COVID-19 pandemic, with a delay in the peak incidence of type 1 diabetes by ∼3 months after the peak COVID-19 incidence and also after pandemic containment measures. The underlying causes are yet unknown. However, indirect rather than direct effects of the pandemic are more likely to be the cause.
Gesehen am 16.09.2022